THE PAST GHOST: THE EXPRESSION OF NARRATIVE IDEOLOGY IN HISTORY TEXTBOOKS DURING THE NEW ORDER AND REFORMASI IN INDONESIA - Darmawan, Wawan; Sjamsuddin, helius; Mulyana, Agus (History Department, Semarang State University and Historian Society of Indonesia, 2018)
Narrative in history textbooks usually refers to the history of Indonesia itself. The written experiences are the stories which are considered as proud for the history of their nation and the government in power. Thus, no wonder if the government changes, the materials which are not in line with the present government will vanish or be eliminated. However, for various topics, this cannot be vanished and changed even though the government changes. This situation looks like a ghost and sometimes can cause fear and anxiety because it comes with a strong figure. The aim of this study is to investigate the narrative expression in the history learning textbooks for Senior High School published in the New Order and Reformasi (reformation) era as ideology. Hence, in order to examine the problem, the researcher used critical discourse analysis method in which its main study was texts. Texts are created in the political and social contexts in which there are social power and domination. The results show that the materials which had vanished and appeared in a different version in the history school textbooks cannot be separated from the influence of the governmentÃ¢â‚¬â„¢s interests or we call it as ideologization in history textbooks. The government in power has an authority with his policy to limit, to add and to eliminate the previous history materials and then interprets himself for an event in the past.Ã‚Â Narasi dalam buku pelajaran sejarah biasanya mengacu pada sejarah Indonesia itu sendiri. Pengalaman tertulis adalah kisah-kisah yang dianggap membanggakan sejarah bangsa mereka dan pemerintah yang berkuasa. Dengan demikian, tidak heran jika pemerintah berubah, bahan-bahan yang tidak sejalan dengan pemerintahan sekarang akan lenyap atau dihilangkan. Namun, untuk berbagai topik, ini tidak dapat dihilangkan dan diubah meskipun pemerintah berubah. Keadaan ini terlihat seperti hantu dan terkadang bisa menimbulkan rasa takut dan kecemasan karena muncul dengan sosok yang kuat. Tujuan dari penelitian ini adalah untuk menyelidiki ekspresi naratif dalam buku teks pembelajaran sejarah untuk Sekolah Menengah Atas yang diterbitkan pada era Orde Baru dan Reformasi sebagai ideologi. Oleh karena itu, untuk menguji masalah, peneliti menggunakan metode analisis wacana kritis di mana studi utamanya adalah teks. Teks dibuat dalam konteks politik dan sosial di mana ada kekuatan dan dominasi sosial. Hasilnya menunjukkan bahwa materi yang telah lenyap dan muncul dalam versi yang berbeda dalam buku pelajaran sekolah sejarah tidak dapat dipisahkan dari pengaruh kepentingan pemerintah atau kita menyebutnya sebagai ideologi dalam buku teks sejarah. Pemerintah yang berkuasa memiliki otoritas dengan kebijakannya untuk membatasi, menambah dan menghilangkan materi sejarah sebelumnya dan kemudian menafsirkan dirinya sendiri untuk suatu peristiwa di masa lalu.Ã‚Â